Leptin Selectively Regulates Nutrients Metabolism in Nile Tilapia Fed on High Carbohydrate or High Fat Diet - Liu, Cai-Zhi; He, An-Yuan; Ning, Li-Jun; Luo, Yuan; Li, Dong-Liang; Zhang, Mei-Ling; Chen, Li-Qiao; Du, Zhen-Yu (Frontiers in Endocrinology, 2018)
Leptin is known to inhibit appetite and promote energy metabolism in vertebrates. Leptin resistance (LR) commonly occurs in diet-induced obesity (DIO) in mammals. However, the roles of leptin in the energy homeostasis in DIO animals with LR remain unclear. Here we first verified the high expression of leptin in subcutaneous adipose tissue as in liver in Nile tilapia. Furthermore, we produced two types of DIO Nile tilapia by using a high-carbohydrate diet (HCD) or a high-fat diet (HFD), and confirmed the existence of LR in both models. Notably, we found that HCD-DIO fish retained leptin action in the activation of lipid metabolism and showed LR in glucose metabolism regulation, while this selective leptin action between lipid and glucose metabolism was reversed in HFD-DIO fish. Fasting the fish for one week completely recovered leptin actions in the regulation of lipid and glucose metabolism. Therefore, leptin may retain more of its activities in animals with LR than previously believed. Evolutionally, this selective regulation of leptin in nutrients metabolism could be an adaptive mechanism in animals to store surplus calories when different types of food are abundant.